Gender-Based Violence on Campus: Patriarchal Power Relations and Masculinity in the Context of Relationship Rejection - Farita Kaila; Nadira Khalisa; Ika Arinia Indriyany (Madani: Jurnal Ilmiah Multidisiplin, 2026)
Gender-based violence occurring within university environments indicates that campus spaces have not yet fully become safe places for women. This study analyzes a case of violence experienced by a female student at Universitas Islam Negeri Sultan Syarif Kasim Riau in 2026 using the perspectives of power relations and hegemonic masculinity. The research employs a qualitative approach with a case study method. Data were obtained through the examination of media reports, academic literature, and reports from official institutions, including Komnas Perempuan (the National Commission on Violence Against Women). The findings show that violence against women cannot be understood merely as an individual criminal act. This phenomenon is also related to patriarchal social structures that place women in more vulnerable positions within society. In addition, discussions that develop on social media often demonstrate a tendency toward victim blaming. Gender-based violence in university environments therefore needs to be understood as a structural issue related to gender power relations and the construction of masculinity in society.